2001
DOI: 10.1136/thorax.56.7.549
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of transforming growth factor beta1 and beta3 mRNA transcripts in normal and fibrotic human lung

Abstract: Background-Transforming growth factor 1 is implicated in the pathogenesis of lung fibrosis. It promotes extracellular matrix accumulation by increasing procollagen synthesis and reducing degradation. TGF 1 gene and protein expression increase in experimental lung fibrosis, and TGF 1 antibodies attenuate fibrosis in mice. The role of other TGF isoforms is unclear. This study aimed to localise TGF 1 and TGF 3 gene expression in fibrotic human lung and compare it with that in normal human lung. Methods-Lung tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 31 publications
5
70
1
1
Order By: Relevance
“…The source of TGF-b in lung tissue and the cells that respond to TGF-b1 during the pathogenesis of tissue fibrosis is unclear, and likely depend on the nature or locale of the insults. Expression of TGF-b occurs in the bronchial epithelium and submucosa of patients with asthma, chronic bronchitis, and fibrosis (42,46). In mice and humans with IPF, the airway epithelium has been suggested to be a major source of TGF-b1 (47,48), although other studies have reported that eosinophils and fibroblasts are a source of TGF-b1 in allergic airway disease (13,49,50).…”
Section: Discussionmentioning
confidence: 97%
“…The source of TGF-b in lung tissue and the cells that respond to TGF-b1 during the pathogenesis of tissue fibrosis is unclear, and likely depend on the nature or locale of the insults. Expression of TGF-b occurs in the bronchial epithelium and submucosa of patients with asthma, chronic bronchitis, and fibrosis (42,46). In mice and humans with IPF, the airway epithelium has been suggested to be a major source of TGF-b1 (47,48), although other studies have reported that eosinophils and fibroblasts are a source of TGF-b1 in allergic airway disease (13,49,50).…”
Section: Discussionmentioning
confidence: 97%
“…Another group failed to show differences in the expression of TGF-β isoforms after bleomycin (Santana et al, 1995). So far, only two studies have analyzed TGF-β3 expression in fibrotic human lung tissue, and both supported a more prominent role for TGF-β1 compared with TGF-β3 (Coker et al, 2001;Khalil et al, 1996). More evidence supporting the hypothesis of TGF-β isoform imbalances in "fibrotic" versus "regular wound healing" can be found in other organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that upregulation of iNOS-induced NO production appears in PF in both animal models and humans (22)(23)(24). Transforming growth factor-β1 (TGF-β1) is well recognized as a key pro-fibrogenetic cytokine in PF, and may result in collagen overproduction and deposition in the lung (25). Elevated expression of TGF-β1 has also been found in the lung tissues of patients and animals with PF (26).…”
Section: Oxymatrine Attenuates Bleomycin-induced Pulmonary Fibrosis Imentioning
confidence: 96%